2012
DOI: 10.1108/17554171211252493
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐taking behaviour of Islamic banks: application of prospect theory

Abstract: PurposeThe paper aims to gain an insight into behavioural characteristics of Islamic banks and how they influence the risk‐taking decisions of Islamic banks in financial markets within the prospect theory context.Design/methodology/approachThe study employs review and application of prospect theory in Islamic banking industry across the globe, making use of 99 Islamic banks across 14 countries.FindingsEmpirical evidence shows that Islamic banks located above target risk level tend to show risk‐adverse behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…Jika regulator memahami bahwa manajer bank mungkin menjadi kurang risk-averse ketika mereka beroperasi di bawah target dan kecenderungan ini meningkat ketika keuntungn mulai menurun. Jika regulator bank sadar akan hubungan ini, mungkin fungsi pengawasan regulasi bank dapat dibuat lebih efektif mencegah lebih banyak kegagalan bank di masa depan (Alam & Boon Tang, 2012).…”
Section: Teori Dan Metodeunclassified
“…Jika regulator memahami bahwa manajer bank mungkin menjadi kurang risk-averse ketika mereka beroperasi di bawah target dan kecenderungan ini meningkat ketika keuntungn mulai menurun. Jika regulator bank sadar akan hubungan ini, mungkin fungsi pengawasan regulasi bank dapat dibuat lebih efektif mencegah lebih banyak kegagalan bank di masa depan (Alam & Boon Tang, 2012).…”
Section: Teori Dan Metodeunclassified
“…Credit Risk is a risk that faced by bank when the financing that given by bank to the customer cannot be paid accordingly (IFSB, 2012;IFSB, 2005). In this research the proxy of credit risk used is Financing to Asset Ratio that has been used by Alam and Tang (2012) who introduced FAR to measure the risk taking behaviour that Islamic bank have taken during the observe period.…”
Section: Literature Review Ifsb Guideline On Risk Managementmentioning
confidence: 99%
“…The risk taking becomes a general preposition because in non-symmetric condition of information, bank managers and / or shareholders tend to prefer a higher level of risk with an expectation of a higher return rate (Taswan, 2009). The amount of risk taken by banks can be measured through Loan to Asset Ratio (LAR) or in Islamic Bank; it is called as Financing to Asset Ratio (Alam & Tang, 2012). Alam and Tang (2012) states that FAR are the ratio used to show the bank's ability to meet customer credit requests based on the total assets owned by bank.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results also support Fiegenbaum and Thomas's (1988) findings. Alam and Boon Tang (2012) showed that Islamic banks located above target risk level tend to show risk-averse behaviour, while banks below target risk level inclined towards risk-seeking attitude. Their results also highlighted that banks which have higher loans to total asset ratio tend to take on lower risk.…”
Section: Literature Reviewmentioning
confidence: 99%